Rethinking children's rights attitudes in contemporary society - Jones, Phil 1958 April 22-; Welch, Susan (New childhoods series, 2018)
"Rethinking Children's Rights explores attitudes towards and experiences of children's rights. Phil Jones and Sue Welch draw on a wide range of thought, research and practice from different fields and countries to debate, challenge and re-appraise long held beliefs, attitudes and ways of working and living with children.This second edition contains updated references to legislation and research underpinning children's rights, reflecting on recent scholarship and on the current world context."--Provided by publisher.